Peningkatan Minat Belajar Seni Tari dengan Pendekatan Cooperative Learning Tipe Jigsaw Pada Siswa Kelas VIII.9 di SMP Negeri 13 Pekanbaru - Junida Muharaini (Instructional Development Journal, 2018)
This study aims to determine the increase in student dance learning outcomes, the low interest in student learning due to the learning atmosphere that is still teacher-centered. Through the application of the jigsaw learning method, it is expected to increase students' interest and activeness, in the process of learning dance which has a positive impact on student learning outcomes. The research subjects were grade VIII.9 students at Pekanbaru State Middle School 13. The method used in collecting data is, observation, interviews and documentation. This research was carried out by carrying out class actions consisting of 2 cycles. The instruments used were observation sheets, assessment sheets, questionnaire questionnaires, interview guidelines and field notes. The results of the study showed that: (1) in the first cycle test students did not understand and could not do the task properly. This first cycle has 15 people who are not in accordance with the value of hope, there are 15 people who have not yet finished. This pattern is indeed easier for students, and according to the way of thinking many people tend to be less good at Lancang Kuning dance dancing, (2) in the second cycle of learning actually serves as a "stimulant" of students' ideas and thoughts. The application of the jigsaw cooperative learning approach in the study would be very appropriate for the Lancang Kuning dance practice. In the practice of dance students are not encountered with errors that are so meaningful as in cycle I. This is reinforced by 40 students fulfilling the criteria complete. (3) the application of the Lancang Kuning dance as an effort to increase the ability of Lancang Kuning dance learning proved significantly to students of Pekanbaru Public Middle School 13.